FAKTOR - FAKTOR YANG MEMENGARUHI PELAYANAN INSTALASI PEMELIHARAAN SARANA DAN PRASARANA DI IGD RUMAH SAKIT UMUM KOTA PINANG KABUPATEN LABUHANBATU SELATAN TAHUN 2020 - yanti, asmima (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Employees in the Hospital Facilities Maintenance Installation who have obligations in planning, organizing, distributing and maintaining hospital facilities. Because realizing quality health services is not only related to the quality of services from the medical but also through the support of staff in the maintenance of medical, non-medical and building equipment. The type of research used in this study is an analytical survey with a cross-sectional study design which aims to analyze the factors that affect the maintenance of facilities and infrastructure for emergency services at the General Hospital of Kota Pinang District, South Labuhanbatu Regency in 2020. The sample in this study were all officers of the facility and infrastructure maintenance installation as well as officers in the IGD of the General Hospital in the District of Kota Pinang, Labuhanbatu Selatan Regency, as many as 38 officers or what is called total sampling. This research was conducted to look at the Factors that Influence Installation of Facilities and Infrastructure Maintenance at IGD General Hospital, Pinang City, Labuhanbatu Selatan Regency in 2020. This type of research. , Budget and education. And the most influential factor is Knowledge obtained by Siq value of 0,000 <p: 0.05 and Calibration obtained by Siq value of 0,000 <from p: 0.05.